ALTERNATIF SKENARIO PEMANFAATAN AIR EMBUNG NELAS BERDASARKAN KARAKTERISTIK KETERSEDIAANNYA - Kiki Frida Sulistyani; Danang Bimo Irianto (Prokons: Jurnal Teknik Sipil, 2021)
Abstract East Nusa Tenggara Province is a province that has many embungs. Embung Nelas, in Lamaknen District, Belu Regencyis planned to meet the water demand of the population and cattle in Makir & Lamaksenulu Village as well as field water demand in Makir Village. Embung Nelas is design by using dependable flow Q 80%. From the calculation, Embung Nelas can meet the water demand in Makir and Lamaksenulu villages until 2040 for a population of 5888 people, 4029 large cattle, 1739 small livestock and 3277 chicken, as well as the irrigation water demand of 23 hectares the Makir Village Considering that the rainy conditions are not the same every year, a water use scenario is made based on the water conditions. There are 4 discharge conditions, dry discharge (Q97.3%), low discharge (Q 80%), normal water discharge (50.7%) and sufficient water discharge (26%). The simulation results in the other 3 scenarios, were obtained for the dry discharge of Embung Nelas in 2040 which was only able to irrigate 76% of raw water and cattle, in normal water conditions it could irrigate 6.6 Ha more fields and in sufficient water it could irrigate 12.9 Ha more fields. Keywords: Embung, Dependable flow, Simulation, Scenario